PENGARUH KEAMANAN PANGAN, KESADARAN KESEHATAN, NILAI YANG DIRASAKAN DAN HARGA TERHADAP NIAT BELI MAKANAN CEPAT SAJI PADA KONSUMEN KFC DI KOTA BANDA ACEH - Lismanizar, Sorayanti Utami (Departemen Manajemen, 2018)
Abstract: This study aims to determine the effect of food security, health awareness, perceived value and price to purchase intentions. The sample used is KFC consumers in Banda Aceh City. Sampling technique with nonprobability sampling and using questionnaire as research instrument. The method of analysis used is multiple linear regression analysis (Multiple Regression), the method of analysis to determine the influence of the variables involved. The results showed that food security, health awareness, perceived value and price have a positive and significant effect on purchasing intention.Keywords: Food Safety, Health Consciousness, Perceived Value, Price, Purchase Intention